PENINGKATAN MANAJEMEN RISIKO KESEHATAN DAN KESELAMATAN KERJA DI TERMINAL PETI KEMAS - Hana Ike Dameria Purba (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2021)
In 2018 a work accident was discovered in Container Terminal which resulted in permanent disability and a financial loss. The purpose of this study was to determine how the implementation of Occupational Health and Safety (OHS) Risk Management in this company. This research is a qualitative research with case study research type. Data collection was done by purposive sampling. The results found that the weakness of the risk management process occurs at several stages. The company has not conducted an evaluation of the risks to determine the level of risk that cannot be tolerated. This has an impact on risk control being not focused on risks that cannot be tolerated. In addition, the risk control process carried out at container loading and unloading services only focused on improving equipment and providing PPE. Parties related to OHS have not considered management improvement which should be the main thing in improving OHS. The integration of the communication and consultation process as well as the monitoring and review in stages of determining the context, hazard identification, risk assessment and risk control were also the weaknesses in the risk management process in this company.